GEOCHEMISTRY OF ECLOGITES OF SOME METAMORPHIC COMPLEXES IN THE USSR - Shatskiy V.S.; Koz'menko O.A.; Sobolev N.V.; Gil'bert A.E.; Orestova I.I. (My University, 1988)
We have analyzed the geochemistry of eclogites from the Kastek, Kirgiz and Atbashi Ranges of the Tien Shan in Kirgizia as well as from the Sulutyube area in northern Kazakhstan. From the data obtained, we conclude that rare-earth elements (REE) concentrations do not markedly change under different metamorphic regimes. Therefore, the results of this study may be used to establish the nature of protoliths of the eclogites studied. Our data indicate that protoliths of eclogites were similar to the basalts of mid-ocean ridges and island arcs and, most likely, were fragments of an oceanic crust.